Influência do laser Er:YAG na adesividade intrarradicular - teste mecânico e microscopia eletrônica de varredura - Machado, Marivaldo Diniz (2009)
Since the advent of dentin adhesive systems, many studies have been conducted to determine the best treatment for dentin surfaces in order to obtain success in the adhesive procedure. The use of acid on dentin is wide-spread for the removal of the smear layer and exposure of the dentinal structure to enable penetration and micro-retention of the adhesive system, resulting in adhesion. However, alternative dental treatments have been suggested in appropriate literature, among them, we have laser irradiation. The goal of this study was evaluate the adhesive system bonding to a composite resin on intrarradicular dentinal surfaces irradiated with Er:YAG laser, associated by acid conditioning. Human root were used, obtained from lower 2nd pay-molar. They received two different treatments prior to the application of the adhesive agent and the composite resin, and divided into 2 groups: G1 (test): laser + acid + adhesive and G2 (control): acid + adhesive. Two specimens of each group were processed and destined for Scanning Electron Microscopy (SEM) for morphological analysis in the intrarradicular dentin surfaces. For the tensile strength test, all the roots were restored, split to the middle third and submitted to the push out test. After mechanic tests, was observed better adhesive performance on the laser/acid group (G1) being significant difference statistical (T Test, Student). The morphological analysis showed for the group 1 a irregular scaly surface, and some obstructed dentinal tubules. The group 2 presented open dentinal tubules and regular intertubular dentin. The results of this in vitro study suggest that irradiation with Er:YAG laser associated to acid conditioning it promotes a morphologic standard in the surface of the intrarradicular dentin that it can intervene positively with the values of resistance union an adhesive system.